INTERIOR DESIGN OF STAIPI ISLAMIC CENTER OFFICE SPACE, BAMBU APUS, EAST JAKARTA - Sarah Aisha; Rafi Mentari; Imam Sumarwoto (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
The Islamic Center, located in Bambu Apus, East Jakarta, is a multifunctional building consisting of a mosque, auditorium, teaching and learning rooms and office space for managers. In this “pengabdian masyarakat”, the focus is office space. This is a concern because of the problem with the arrangement of the office space that cannot be fully functioned because there is no arrangement and/or interior design for the office space. Thus, the office space that should accommodate activities for users is not yet usable. Seeing these conditions, we, as a “pengabdian masyarakat” team at Universitas Indraprasta PGRI, are trying to hold discussions and coordinate with the Chairperson of PP Persis Jakarta and do “pengabdian masyarakat” which focusing on architecture design.